Reading Intervention for Students with ASD in the Middle Grades: An Alternating Treatment Study of Embedded Interests Reading and Expository Text Conditions. (2nd January 2022) - Solis, Michael; Reutebuch, Colleen K.; Falcomata, Terry; Jimenez, Zaira; Cravalho, Danielle
ABSTRACT: Aim: We conducted two separate but related multiple baseline with alternating treatment single-case design studies to investigate the effect of the same reading intervention for students with autism spectrum disorder being implemented under different conditions.  Method: We conducted a researcher-implemented study in a public school (Study 1) and a teacher-implemented study in a specialized private charter school for children with ASD (Study 2). In each study, we compared a typical intervention approach with interest-based text intervention that included reading on each child's interest area. The treatment included systematic vocabulary instruction and main-summarization strategy instruction.  Results: Findings from Study One showed consistent increases in comprehension and vocabulary outcomes compared to baseline. In Study Two the baselines phases were unstable with small differences in mean scores detected for vocabulary during the intervention phase favoring the interest-based treatment for three of four participants. Conclusion: The results across studies were mixed indicating the importance of taking into account contextual factors including student characteristics and learning environment.